Prevalence of Childhood and Adolescent Overweight and Obesity from 2003 to 2010 in an Integrated Health Care Delivery System. (18th July 2013) - Gee, Scott; Chin, Debbie; Ackerson, Lynn; Woo, Dewey; Howell, Amanda
Abstract : An observational study of the Kaiser Permanente Northern California (KPNC) BMI coding distributions was conducted to ascertain the trends in overweight and obesity prevalence among KPNC members aged 2–19 between the periods of 2003–2005 and 2009-2010. A decrease in the prevalence of overweight (−11.1% change) and obesity (−3.6% change) and an increase in the prevalence of healthy weight (+2.7% change) were demonstrated. Children aged 2–5 had the greatest improvement in obesity prevalence (−11.5% change). Adolescents aged 12–19 were the only age group to not show a decrease in obesity prevalence. Of the racial and ethnic groups, Hispanics/Latinos had the highest prevalence of obesity across all age groups. The KPNC prevalence of overweight and obesity compares favorably to external benchmarks, although differences in methodologies limit our ability to draw conclusions. Physician counseling as well as weight management programs and sociodemographic factors may have contributed to the overall improvements in BMI in the KPNC population. Physician training, practice tools, automated BMI reminders and performance feedback improved the frequency and quality of physician counseling. BMI screening and counseling at urgent visits, in addition to well-child care visits, increased the reach and dose of physician counseling.